Situation Report: Poland, 15 January 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Martial Law: A Chronology of Events Poland Faces a Bleak Year The Soviet Union Extends Economic Aid to Poland Authorities Mount a Propaganda Campaign of Self-Justification Price Increases Announced Pacification of the Universities Leader of Suspended Solidarity Retracts Statement Made under Duress